Impact of Inflation and Interest Rate Volatility on Corporate Capital Structure Decisions - Budianto, Hendy (Jurnal Informatika Ekonomi Bisnis, 2025)
This study investigates the impact of inflation rate and interest rate volatility on corporate capital structure decisions, emphasizing the mediating role of corporate profitability. Using a quantitative approach and structural equation modeling via SmartPLS, data from publicly listed firms in emerging markets were analyzed to examine the relationships between IR, CP, debt ratio, and equity ratio. The results reveal that IR significantly affects CP, which in turn influences both DR and ER. Direct effects show that IR positively correlates with DR and negatively with ER. Furthermore, CP mediates the relationship between IR and both components of capital structure, indicating that firms with higher profitability are better positioned to respond to macroeconomic shocks by optimizing their financing mix. These findings contribute to a more nuanced understanding of capital structure behavior, highlighting the interplay between external economic conditions and internal financial performance in shaping strategic financing decisions.